Pengaruh Pemanfaatan E-commerce terhadap Pemulihan Ekonomi Pasca Pandemi Covid-19 di Kota Pematang Siantar: Studi Kasus pada Pelaku UMKM - Rizki Alfadillah Nasution; Ilham Syahputra Saragih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The global spread of the Covid-19 pandemic has reached nearly all parts of the world, resulting in severe disruptions and instability within the global economic structure. The response to this phenomenon includes the implementation of Large-Scale Social Restrictions (PSBB), which significantly affects the Micro, Small, and Medium Enterprises (MSMEs) sector on a massive scale. MSMEs play a crucial role in the growth and development of Indonesia's economy. Considering this context, the primary objective of this research is to explore the contribution made by E-Commerce to the efforts of economic recovery for MSMEs in the aftermath of the Covid-19 pandemic in the region of Pematang Siantar City. The applied research methodology involves the collection of both primary and secondary data. Primary data is obtained through the distribution of questionnaires using both conventional and online methods. On the other hand, secondary data is gathered through an in-depth review of relevant scholarly literature and research journals related to the subject. This study is specifically conducted in the Pematang Siantar City region, North Sumatra, with a data collection period spanning 20 days. The findings of this study indicate that elements such as Income Growth (P=0.679), Increased Market Access (P=0.302), Product Innovation & Diversification (P=0.756), and Job Creation (P=0.294) do not have a significant impact on the process of economic recovery for MSMEs in the Pematang Siantar City region.